Difunctional nanosheet as well as preparation method and application thereof
By preparing MgSrCeAl-LDH nanosheets, using their dual functions in ROS clearance and angiogenesis, the problems of oxidative stress and angiogenesis in reperfusion injury were solved, and the recovery effect after myocardial injury was significantly improved.
Patent Information
- Application Number
- CN202411253641.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
Reperfusion injury still has a high incidence in the treatment of ischemic heart disease, especially because myocardial ischemia/reperfusion injury (MIRI) caused by oxidative stress is difficult to effectively prevent and treat. Existing nanomaterials are removing reactive oxygen species (ROS) and limited performance in promoting angiogenesis.
The bifunctional nanosheet MgSrCeAl-LDH was prepared by co-precipitation reaction, combining layered bimetallic hydroxides of magnesium, aluminum, cerium and strontium, and using the superoxide dismutase activity of Ce3+ and the pro-angiogenic properties of Sr2+, it was designed. Nanosheets with efficient ROS clearance and angiogenesis capabilities.
It significantly improved the survival rate of cardiomyocytes and endothelial cells, reduced oxidation level and apoptosis rate, significantly improved cardiac function recovery, improved vascular formation ability, and effectively alleviated myocardial injury after MIRI.
Smart Images

Figure CN119113144A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of nano functional materials, and in particular to a dual-functional nano sheet and a preparation method and application thereof. Background Art
[0002] The morbidity and mortality of ischemic heart disease are increasing year by year, among which acute myocardial infarction is the most fatal. Reperfusion is an important means to quickly restore coronary blood flow in ischemic hearts. Timely and effective reperfusion therapy is crucial to saving ischemic myocardium and limiting the area of infarction. However, revascularization promoted by reperfusion induces myocardial post-ischemic injury and complications. This phenomenon in which myocardial tissue damage is aggravated after blood flow is restored on the basis of ischemia, and even irreversible damage occurs is called myocardial ischemia / reperfusion injury (MIRI). With the promotion and application of technologies such as extracorporeal circulation, coronary artery bypass grafting, congenital heart disease correction, and valve replacement, reperfusion injury has become a major problem affecting the efficacy of cardiovascular surgery. Despite the emergence of more effective reperfusion techniques such as ischemic preconditioning and ischemic postconditioning, and drugs to improve reperfusion injury, the incidence of secondary myocardial injury after blood flow restoration is still high due to the narrow intervention window and individual differences in susceptibility to reperfusion injury. Therefore, the prevention and treatment measures and the occurrence mechanism of MIRI have always been a hot topic in the cardiovascular field.
[0003] MIRI is a complex process involving a series of pathological changes such as oxidative stress, calcium overload, energy metabolism disorders and inflammatory cell activation. Oxidative stress runs through the entire process of MIRI occurrence and development, and reactive oxygen species (ROS, including ·OH, ·O2 - , 1 The massive accumulation of ROS (such as O2, H2O2, etc.) is considered to be the main factor of MIRI. The ROS burst is mainly attributed to the electron leakage mediated by the damaged electron transport chain and the reduced mitochondrial oxidative phosphorylation activity during the MIRI process. The massive accumulation of ROS leads to: ① Oxidative damage to DNA and proteins, inducing cardiovascular cell apoptosis; ② Destruction of the antioxidant system, inducing imbalance of the internal environment homeostasis; ③ Proteolytic enzymes produced by auxiliary infiltration attack adjacent cardiomyocytes, aggravating myocardial damage; ④ Lipid peroxidation, activating the ferroptosis cascade reaction. Previous studies have also shown that after simulating MIRI in vitro using oxygen-glucose deprivation / re-glucose-reoxygenation (OGD / R), PI3K-Akt, MAPK, and Ca 2+ This suggests that the progression of MIRI is closely related to the accumulation of ROS, and targeted ROS clearance may effectively solve the problem of MIRI by regulating pathological reactions such as apoptosis, immunity, and myocardial fibrosis induced by ROS.
[0004] Nanomaterials have shown great application prospects in the biomedical field due to their excellent biosafety, high stability and multifunctional design. Antioxidant therapy based on nanomaterials has also been deeply explored in the treatment of oxidative damage heart disease. At present, a variety of nanosheets have been developed to alleviate ischemia-reperfusion injury, such as Mxene nanosheets, cerium oxide nanosheets, manganese oxide nanosheets and iron oxide nanosheets. Among them, cerium oxide has attracted widespread attention due to its large number of oxygen vacancy defects, suggesting that Ce-based 3+ / Ce 4+ The strategy of rapid conversion and efficient ROS removal may have good prospects in alleviating MIRI. Although a variety of Ce-based nanosystems have been developed, their research in the biomedical field is still in its infancy, ultimately resulting in limited ability to remove ROS and angiogenesis. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a dual-functional nanosheet and a preparation method and application thereof. The dual-functional nanosheet of the present invention can efficiently remove ROS and promote angiogenesis.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The invention provides a method for preparing a bifunctional nanosheet, comprising the following steps:.
[0008] Mixing a soluble magnesium salt, a soluble strontium salt, a soluble cerium salt, a soluble aluminum salt and water to obtain a metal salt solution;
[0009] The metal salt solution and the inorganic alkali solution are simultaneously added dropwise to the sodium nitrate solution to carry out a coprecipitation reaction, thereby obtaining the bifunctional nanosheet.
[0010] Preferably, the soluble magnesium salt comprises magnesium nitrate, the soluble strontium salt comprises strontium nitrate, the soluble cerium salt comprises cerium nitrate, and the soluble aluminum salt comprises aluminum nitrate.
[0011] Preferably, in the metal salt solution, the molar ratio of the soluble magnesium salt, the soluble strontium salt, the soluble cerium salt and the soluble aluminum salt is 2:0.2:0.1-0.75:0.05-0.7.
[0012] Preferably, in the metal salt solution, the total concentration of the soluble magnesium salt, the soluble strontium salt, the soluble cerium salt and the soluble aluminum salt is 0.1 to 0.3 mol / L.
[0013] Preferably, the concentration of the inorganic alkali solution is 0.1-0.4 mol / L; the inorganic alkali in the inorganic alkali solution includes sodium hydroxide.
[0014] Preferably, the concentration of the sodium nitrate solution is 0.1-0.3 mol / L.
[0015] Preferably, the volume ratio of the metal salt solution, the inorganic alkali solution and the sodium nitrate solution is 1:1:1.
[0016] Preferably, the coprecipitation reaction is carried out at room temperature and for 20 to 30 minutes.
[0017] The present invention also provides a bifunctional nanosheet prepared by the preparation method described in the above technical solution. The bifunctional nanosheet has a sheet-like morphology, a particle size of 100 nm, and a thickness of 3 nm.
[0018] The present invention also provides the use of the bifunctional nanosheet described in the above technical solution in the preparation of a therapeutic preparation for myocardial ischemia-reperfusion injury.
[0019] The invention provides a method for preparing a dual-functional nanosheet.
[0020] Layered double hydroxides (LDHs) are a type of anionic inorganic layered crystal materials, which are composed of a highly ordered and positively charged main layer plate and anions uniformly distributed and negatively charged interlayer anions. The anions and cations are neutralized to make the crystal electrically neutral. The present invention uses a double drop method to prepare magnesium aluminum hydrotalcite (MgAl-LDH) as the main layer plate, and introduces the bioactive component Ce into the main layer plate. 3+ and Sr 2+ , and then developed a dual-functional nanosheet that can accurately and efficiently remove ROS and promote angiogenesis (hereinafter referred to as MgSrCeAl-LDH nanosheet). In the MgSrCeAl-LDH nanosheet, Ce 3+ and Sr 2+ The presence of SOD makes it have superoxide dismutase activity and angiogenesis-promoting properties. The fully exposed active sites on the surface of the nanosheets can effectively remove ROS, regulate the hypoxic microenvironment, and release Sr in response to the ischemic acidic microenvironment. 2+ , promoting endothelial cell proliferation and migration, and facilitating angiogenesis. Its use in MIRI treatment has the following advantages:
[0021] (1) The MgSrCeAl-LDH nanosheets of the present invention have an ultra-thin layered two-dimensional structure, and a large number of metal active sites can be exposed on the surface, which is beneficial to the adsorption of ROS molecules and enhances their enzyme activity in the ischemia-reperfusion microenvironment.
[0022] (2) The MgSrCeAl-LDH nanosheets of the present invention have high biocompatibility and can achieve controllable release of bioactive ions in response to the ischemic acidic microenvironment.
[0023] (3) The MgSrCeAl-LDH nanosheets of the present invention significantly improve the effect of alleviating oxygen-glucose deprivation of cardiomyocytes and endothelial cells. At a concentration of 10 μg / mL, the cell survival rate is increased to about 90%, the intracellular oxidation level and apoptosis level are significantly reduced, and the angiogenesis ability is significantly improved.
[0024] (4) The MgSrCeAl-LDH nanosheets of the present invention have a significant effect on restoring the cardiac function of MIRI rats. When 30 μL of the MgSrCeAl-LDH nanosheet dispersion was injected in situ, the cardiac function was significantly improved on the 7th and 14th days after MIRI. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Mg2Sr obtained in Example 3 0.2 Ce 0.7 Al 0.1 - Transmission electron microscopy image of LDH nanosheets;
[0026] Figure 2 Mg2Sr obtained in Example 3 0.2 Ce 0.7 Al 0.1 -Atomic force microscopy image of LDH nanosheets;
[0027] Figure 3 Mg2Sr obtained in Example 3 0.2 Ce 0.7 Al 0.1 - Particle size distribution of LDH nanosheets within 7 days;
[0028] Figure 4 This is a graph showing the superoxide anion consumption performance of the MgSrCeAl-LDH nanosheets obtained in Examples 1 to 5;
[0029] Figure 5 This is a performance diagram of hydroxyl radical consumption of MgSrCeAl-LDH nanosheets obtained in Examples 1 to 5;
[0030] Figure 6 Mg2Sr obtained in Example 3 0.2 Ce 0.7 Al 0.1 -LDH in different pH conditions 2+ Release curve diagram;
[0031] Figure 7 Mg2Sr obtained in Example 3 0.2 Ce 0.7 Al 0.1 -Biological safety evaluation study diagram of LDH;
[0032] Figure 8Mg2Sr obtained in Example 3 0.2 Ce 0.7 Al 0.1 -In vitro effectiveness study of LDH nanosheets;
[0033] Fig. 9 Mg2Sr obtained in Example 3 0.2 Ce 0.7 Al 0.1 -Figure of in vivo effectiveness study of LDH nanosheets. DETAILED DESCRIPTION
[0034] The present invention provides a method for preparing a bifunctional nanosheet, comprising the following steps:
[0035] Mixing a soluble magnesium salt, a soluble strontium salt, a soluble cerium salt, a soluble aluminum salt and water to obtain a metal salt solution;
[0036] The metal salt solution and the inorganic alkali solution are simultaneously added dropwise to the sodium nitrate solution to carry out a coprecipitation reaction, thereby obtaining the bifunctional nanosheet.
[0037] In the present invention, unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0038] The invention mixes soluble magnesium salt, soluble strontium salt, soluble cerium salt, soluble aluminum salt and water to obtain a metal salt solution.
[0039] In the present invention, the soluble magnesium salt preferably includes magnesium nitrate (Mg(NO3)2). In the present invention, the soluble strontium salt preferably includes strontium nitrate (Sr(NO3)2). In the present invention, the soluble cerium salt preferably includes cerium nitrate (Ce(NO3)3). In the present invention, the soluble aluminum salt preferably includes aluminum nitrate (Al(NO3)3). In the present invention, the water is preferably deionized water.
[0040] In the present invention, the mixing of the soluble magnesium salt, the soluble strontium salt, the soluble cerium salt, the soluble aluminum salt and water is preferably carried out under ultrasonic stirring.
[0041] In the present invention, in the metal salt solution, the molar ratio of the soluble magnesium salt, the soluble strontium salt, the soluble cerium salt and the soluble aluminum salt is preferably 2:0.2:0.1-0.75:0.05-0.7.
[0042] In the present invention, in the metal salt solution, the total concentration of the soluble magnesium salt, the soluble strontium salt, the soluble cerium salt and the soluble aluminum salt is preferably 0.1 to 0.3 mol / L, more preferably 0.3 mol / L.
[0043] After obtaining the metal salt solution, the present invention simultaneously drops the metal salt solution and the inorganic alkali solution into the sodium nitrate solution to carry out a coprecipitation reaction to obtain the bifunctional nanosheet.
[0044] In the present invention, the concentration of the inorganic alkali solution is preferably 0.1-0.4 mol / L, more preferably 0.2 mol / L; the inorganic alkali in the inorganic alkali solution preferably includes sodium hydroxide. The present invention does not specifically limit the preparation method of the inorganic alkali solution.
[0045] In the present invention, the concentration of the sodium nitrate solution is preferably 0.1 to 0.3 mol / L, and more preferably 0.2 mol / L. The present invention does not specifically limit the preparation method of the sodium nitrate solution.
[0046] In the present invention, the volume ratio of the metal salt solution, the inorganic alkali solution and the sodium nitrate solution is preferably 1:1:1.
[0047] In the present invention, the temperature of the coprecipitation reaction is preferably room temperature, and the time is preferably 20 to 30 minutes. In the present invention, the coprecipitation reaction is preferably carried out under stirring. In the present invention, the time of the coprecipitation reaction is preferably started after the metal salt solution and the inorganic base solution are completely added.
[0048] In the present invention, the bifunctional nanosheets are preferably in the form of a bifunctional nanosheet dispersion, and the dispersant of the bifunctional nanosheet dispersion is preferably deionized water.
[0049] After the coprecipitation reaction, the present invention preferably further comprises: centrifuging the obtained coprecipitation reaction liquid, collecting the precipitate, and centrifugally washing the precipitate to obtain the bifunctional nanosheet; and dispersing the bifunctional nanosheet in deionized water to obtain a bifunctional nanosheet dispersion. In the present invention, the reagent for the centrifugal washing preferably comprises an ethanol-deionized water mixed solution or deionized water.
[0050] The present invention also provides a bifunctional nanosheet (hereinafter referred to as MgSrCeAl-LDH nanosheet) prepared by the preparation method described in the above technical solution. The bifunctional nanosheet has a sheet-like morphology, a particle size of 100 nm, and a thickness of 3 nm.
[0051] The present invention also provides the use of the bifunctional nanosheet described in the above technical solution in the preparation of a therapeutic preparation for myocardial ischemia-reperfusion injury.
[0052] The present invention does not specifically limit the application method of the bifunctional nanosheets, and operations familiar to those skilled in the art may be used.
[0053] The bifunctional nanosheets provided by the present invention and their preparation methods and applications are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0054] Example 1
[0055] (1) Dissolve magnesium nitrate, strontium nitrate, cerium nitrate and aluminum nitrate in deionized water, and mix them evenly by ultrasonication and stirring to obtain a metal salt solution; in the metal salt solution, the molar ratio of magnesium nitrate, strontium nitrate, cerium nitrate and aluminum nitrate is 2:0.2:0.3:0.5, and the total concentration of magnesium nitrate, strontium nitrate, cerium nitrate and aluminum nitrate is 0.3 mol / L.
[0056] (2) Dissolve sodium hydroxide in deionized water, sonicate and stir to dissolve, and obtain a sodium hydroxide solution with a concentration of 0.4 mol / L.
[0057] (3) Dissolve sodium nitrate in deionized water, sonicate and stir to dissolve, and obtain a sodium nitrate solution with a concentration of 0.2 mol / L.
[0058] 10 mL of the metal salt solution of step (1) and 10 mL of the sodium hydroxide solution of step (2) were simultaneously added dropwise to 10 mL of the sodium nitrate solution of step (3). After the addition was completed, the mixture was stirred for 30 min at room temperature under N2 conditions. After the reaction was completed, the mixture was centrifuged to collect the precipitate. The precipitate was washed with deionized water by centrifugation to obtain Mg2Sr 0.2 Ce 0.3 Al 0.5 -LDH nanosheets, added with deionized water to prepare Mg2Sr 0.2 Ce 0.3 Al 0.5 -LDH dispersion.
[0059] Example 2
[0060] (1) Dissolve magnesium nitrate, strontium nitrate, cerium nitrate and aluminum nitrate in deionized water, and mix them evenly by ultrasonication and stirring to obtain a metal salt solution; in the metal salt solution, the molar ratio of magnesium nitrate, strontium nitrate, cerium nitrate and aluminum nitrate is 2:0.2:0.5:0.3, and the total concentration of magnesium nitrate, strontium nitrate, cerium nitrate and aluminum nitrate is 0.3 mol / L.
[0061] (2) Dissolve sodium hydroxide in deionized water, sonicate and stir to dissolve, and obtain a sodium hydroxide solution with a concentration of 0.4 mol / L.
[0062] (3) Dissolve sodium nitrate in deionized water, sonicate and stir to dissolve, and obtain a sodium nitrate solution with a concentration of 0.2 mol / L.
[0063] 10 mL of the metal salt solution of step (1) and 10 mL of the sodium hydroxide solution of step (2) were simultaneously added dropwise to 10 mL of the sodium nitrate solution of step (3). After the addition was completed, the mixture was stirred for 30 min at room temperature under N2 conditions. After the reaction was completed, the mixture was centrifuged to collect the precipitate. The precipitate was washed with deionized water by centrifugation to obtain Mg2Sr 0.2 Ce 0.5 Al 0.3 -LDH nanosheets, added with deionized water to prepare Mg2Sr 0.2 Ce 0.5 Al 0.3 -LDH dispersion.
[0064] Example 3
[0065] (1) Dissolve magnesium nitrate, strontium nitrate, cerium nitrate and aluminum nitrate in deionized water, and mix them evenly by ultrasonication and stirring to obtain a metal salt solution; in the metal salt solution, the molar ratio of magnesium nitrate, strontium nitrate, cerium nitrate and aluminum nitrate is 2:0.2:0.7:0.1, and the total concentration of magnesium nitrate, strontium nitrate, cerium nitrate and aluminum nitrate is 0.3 mol / L.
[0066] (2) Dissolve sodium hydroxide in deionized water, sonicate and stir to dissolve, and obtain a sodium hydroxide solution with a concentration of 0.4 mol / L.
[0067] (3) Dissolve sodium nitrate in deionized water, sonicate and stir to dissolve, and obtain a sodium nitrate solution with a concentration of 0.2 mol / L.
[0068] 10 mL of the metal salt solution of step (1) and 10 mL of the sodium hydroxide solution of step (2) were simultaneously added dropwise to 10 mL of the sodium nitrate solution of step (3). After the addition was completed, the mixture was stirred for 30 min at room temperature under N2 conditions. After the reaction was completed, the mixture was centrifuged to collect the precipitate. The precipitate was washed with deionized water by centrifugation to obtain Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH nanosheets, added with deionized water to prepare Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH dispersion.
[0069] Example 4
[0070] The difference from Example 1 is that in step (1), the molar ratio of magnesium nitrate, strontium nitrate, cerium nitrate and aluminum nitrate in the metal salt solution is 2:0.2:0.1:0.7 to obtain Mg2Sr 0.2 Ce 0.1 Al 0.7 -LDH nanosheets.
[0071] Example 5
[0072] The difference from Example 1 is that in step (1), the molar ratio of magnesium nitrate, strontium nitrate, cerium nitrate and aluminum nitrate in the metal salt solution is 2:0.2:0.75:0.05 to obtain Mg2Sr 0.2 Ce 0.75 Al 0.05 -LDH nanosheets.
[0073] Figure 1 Mg2Sr prepared in Example 3 0.2 Ce 0.7 Al 0.1 - Transmission electron microscopy image of LDH nanosheets, from Figure 1 It can be seen that Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH has a round flake structure with a diameter of about 100nm.
[0074] Figure 2 Mg2Sr prepared in Example 3 0.2 Ce 0.7 Al 0.1 -Atomic force microscopy images of LDH nanosheets, where the left image is Mg2Sr 0.2 Ce 0.7 Al 0.1 -AFM images of LDH nanosheets, the right image is Mg2Sr 0.2 Ce 0.7 Al 0.1 -Height analysis curve of LDH nanosheets, from Figure 2 It can be seen that the average thickness of MgSrCeAl-LDH nanosheets is about 5 nm.
[0075] Figure 3 Mg2Sr prepared in Example 3 0.2 Ce 0.7 Al 0.1 - Particle size distribution of LDH nanosheets within 7 days, from Figure 3 It can be seen that Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH nanosheets in different media (water, DMEM and PBS) for 7 days after Mg2Sr 0.2 Ce 0.7 Al 0.1 The size of the -LDH nanosheets hardly changed, indicating their good colloidal stability.
[0076] The MgSrCeAl-LDH nanosheets prepared in the above Examples 1 to 5 were used to test the ROS consumption capacity. The process was as follows: the MgSrCeAl-LDH nanosheets prepared in the above Examples 1 to 5 were added to a microenvironment simulating ROS release, and the inhibitory effect of the MgSrCeAl-LDH nanosheets on ROS was observed. At the same time, the ratio of divalent metal to trivalent metal was changed to observe the difference in the final performance. The results are as follows: Figure 4 and Figure 5 shown.
[0077] Figure 4 The superoxide anion consumption performance diagram of the MgSrCeAl-LDH nanosheets prepared in Examples 1 to 5 is shown in FIG. Figure 4 It can be seen that Fe 2+ +H2O2, that is, the Fenton group that produces ·OH, has a stronger ·OH signal peak, while in Mg2Sr 0.2 Ce 0.7 Al 0.1 The ESR signal in the -LDH group was very weak and significantly weaker than that of the commercial CeO2 nanozyme, indicating that MgSrCeAl-LDH had excellent ·OH scavenging performance.
[0078] Figure 5 The hydroxyl radical consumption performance diagram of the MgSrCeAl-LDH nanosheets prepared in Examples 1 to 5 is shown in FIG. Figure 5 It can be seen that the electron spin resonance (ESR) spectrum detected the MgSrCeAl-LDH and CeO2 to O2 - It has a scavenging effect. It reacts with xanthine and xanthine oxidase system to produce O2 - Compared with the control group and CeO2 group, Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH signal intensity is the lowest, indicating that Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH has excellent O2 - Cleansing effect.
[0079] The Mg2Sr obtained in Example 3 0.2 Ce 0.7 Al 0.1 -LDH promotes angiogenesis through biological activity of Sr 2+ The release process is as follows: Mg2Sr obtained in Example 3 0.2 Ce 0.7 Al 0.1 -LDH was immersed in phosphate buffer solutions of different pH values (5.0, 6.5, and 7.4), and the supernatant was taken by regular centrifugation. The Sr at different time points was detected by ICP technology.2+ The results are as follows Figure 6 As shown, Figure 6 Mg2Sr obtained in Example 3 0.2 Ce 0.7 Al 0.1 -LDH in different pH conditions 2+ Release curve diagram. Figure 6 It can be seen that under acidic conditions, Sr 2+ The Sr detected under neutral conditions was continuously released over time. 2+ The amount of Mg2Sr can be ignored. 0.2 Ce 0.7 Al 0.1 -LDH has acid-responsive release of Sr 2+ properties, thereby promoting angiogenesis.
[0080] Test Example 1 Biosafety Evaluation Study
[0081] 1. Hemolytic study: Add appropriate and equal amounts of 2% red blood cell suspension into several 1.5mL PE tubes, and then add distilled water, PBS, Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH dispersion (40 μg / mL, 80 μg / mL, 120 μg / mL, 160 μg / mL, 200 μg / mL) was mixed and immediately placed in a constant temperature water bath at (37±0.5)°C for incubation, and the hemolysis of each tube was observed and recorded.
[0082] 2. In vitro biocompatibility study: CCK-8 test was used to investigate the toxic effects of LDHs-based nanosheets on H9c2 and MCMEC cells. The specific steps were as follows: a control group (Control group), Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH nanosheet group (LDH group) (10 μg / mL, 20 μg / mL, 30 μg / mL, 40 μg / mL, 50 μg / mL, 60 μg / mL, 80 μg / mL, 100 μg / mL) with a total of 9 different groups. H9c2 and MCMEC cells with good growth status in the logarithmic growth phase were taken and cultured at 1×10 4 / well was inoculated in a 96-well plate, with 6 replicate wells in each group. After culturing for 24 hours under normal conditions, different concentrations of nanosheet solutions were added and incubated together for another 24 hours. Subsequently, 10 μL of CCK-8 solution and 90 μL of basal culture medium were added to each well, and incubated at 37°C in the dark for 0.5 to 2 hours. The culture plate was removed, and the absorbance of each well at a wavelength of 450 nm was detected using an ELISA reader to calculate the cell survival rate and draw a cell growth curve.
[0083] 3. In vivo biocompatibility study: 8-week-old male SD rats were fed with a normal diet for 1 week and then anesthetized with isoflurane. They were fixed on the animal experimental table in the supine position, and the skin above the xiphoid process was prepared and disinfected with iodine. A thoracotomy was made in the fourth intercostal space on the left side of the sternum, and positive pressure artificial respiration was performed with a DW-3000B rat ventilator to maintain respiratory continuity and normal pCO2, pO2 and pH values. The great cardiac vein between the left atrial appendage and the conus arteriosus was used as a landmark, and the needle was inserted 2 to 3 mm below the lower edge of the left atrial appendage, and 30 μL Mg2Sr was injected in situ 0.2 Ce 0.7 Al 0.1 -LDH dispersion or PBS solution, routinely close the chest and squeeze the chest during closing to avoid pneumothorax, suture the incisions in each layer, spray an appropriate amount of penicillin powder on the sutured incisions, and disinfect with iodine tincture after suturing. Remove the endotracheal tube after the heartbeat returns to normal, continue to feed for 14 days, observe and record the body weight and death, and take various organs (including heart, liver, spleen, lung and kidney) for H&E staining on the 14th day after intervention, and take blood for biochemical analysis of liver and kidney function indicators.
[0084] The results are as follows Figure 7 As shown, Figure 7 Mg2Sr obtained in Example 3 0.2 Ce 0.7 Al 0.1 -Biological safety evaluation research diagram of LDH nanosheets. Figure 7 A is the detection of Mg2Sr by microplate reader 0.2 Ce 0.7 Al 0.1 -Hemolytic test diagram of LDH nanosheets, Figure 7 B is Mg2Sr detected by UV spectrophotometer 0.2 Ce 0.7 Al 0.1 -Hemolytic test of LDH nanosheets. The results show that when red blood cells are exposed to nanosheets at a concentration of 40 to 200 μg / mL, the hemolysis rate of red blood cells within 3 hours is lower than the 5% specified by the international standard, indicating that the nanosheets have little effect on the integrity of red blood cells; Figure 7 C is Mg2Sr detected by CCK-8 reagent 0.2 Ce 0.7 Al 0.1 - Cytocompatibility test of LDH nanosheets. The results show that H9C2 and MCMECs cells were exposed to nanosheets at a concentration of 10 to 100 μg / mL for 24 hours. Even at the highest tested concentration of 100 μg / mL, the cell viability of H9C2 cells and MCMECs remained at about 90% of that of the control group; Figure 7D is the detection of Mg2Sr by H&E staining 0.2 Ce 0.7 Al 0.1 -LDH nanosheets (corresponding to LDH in Figure D) in vivo safety test results show that Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH nanosheets have no obvious toxicity to the main organs of rats such as heart, liver, spleen, lungs and kidneys. Figure 7 EH for the evaluation of Mg2Sr using biochemical tests 0.2 Ce 0.7 Al 0.1 -LDH nanosheets (corresponding to LDH in Figure EH) in vivo safety test results show that Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH nanosheets had no effect on rat liver function (ALT, AST), renal function (UREA) and hemoglobin level (HGB). Figure 7 It can be seen that Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH nanosheets have good biocompatibility.
[0085] Test Example 2 In vitro effectiveness study
[0086] 1. Study on ROS scavenging performance: DCFH-DA staining method was used to investigate the ROS scavenging performance of Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH nanosheets on the ROS levels of cardiomyocytes and endothelial cells after OGD / R. The specific steps are as follows: a control group (Control group), an oxygen-glucose deprivation / reoxygenation group (OGD / R group), and a Mg2Sr 0.2 Ce 0.7 Al 0.1 There were three different groups of OGD / R+LDH nanosheet treatment groups. Myocardial cells and endothelial cells with good growth status in the logarithmic growth phase were selected and cultured at 2×10 5 / well were inoculated in 12-well plates and cultured under normal conditions for 24 hours. Then, the original culture medium in the 12-well plates was removed. The OGD / R group and the OGD / R+LDH group were stimulated with oxygen and glucose deprivation. After 24 hours, glucose and oxygen were restored. Mg2Sr was added to the OGD / R+LDH group during glucose and oxygenation. 0.2 Ce 0.7 Al 0.1-LDH nanosheet dispersion was co-incubated with cells, and finally DCFH-DA staining was performed. The cell status of each group was observed using a confocal fluorescence microscope, and the intracellular ROS level was quantitatively analyzed using ImageJ software.
[0087] 2. Research on angiogenesis-promoting properties:
[0088] (1) Scratch healing experiment: a control group (Control group), an oxygen-glucose deprivation / re-glucose reoxygenation group (OGD / R group), and a Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH nanosheet treatment group (OGD / R+LDH group) had 3 different groups. First, use a marker pen to draw horizontal lines evenly on the back of the 6-well plate with a ruler, one line every 0.5 cm, and cross the holes. Then, take MCMEC cells with good growth status in the logarithmic growth phase and use 1×10 6 / well were inoculated in 6-well plates and cultured under normal conditions for 24 h. Then, the original culture medium in the 6-well plates was removed. The OGD / R group and the OGD / R+LDH group were stimulated with hypoxia and glucose deprivation. After 24 h, the cells were scratched vertically along the horizontal line on the back. The cells were washed 3 times with PBS to remove floating cells, and then re-glucose and re-oxygenated. Mg2Sr was added to the OGD / R+LDH group during re-glucose and re-oxygenation. 0.2 Ce 0.7 Al 0.1 -LDH nanosheet dispersion was co-incubated with cells, and the average scratch area at multiple observation points at 24h and 48h was calculated to obtain the percentage of scratch area of each group of cells, clarifying the effect of nanosheets on the migration ability of endothelial cells.
[0089] (2) Tube formation experiment: a control group (Control group), an oxygen-glucose deprivation / re-glucose reoxygenation group (OGD / R group), and a Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH nanosheet treatment group (OGD / R+LDH group) was divided into 3 different groups. Prepare 24-well plates and the required consumables, pre-cool them on ice, spread 200 μL Matrigel on each well, place them in a 37°C incubator, and solidify for 30 minutes. Take the cell suspension of each group and add 1×10 5 / well of a 24-well plate, and 6 h later 2+ The cells were washed three times with D-Hanks balanced salt solution, and the tubule formation was recorded using an inverted microscope, and the total length of the tubules and the number of nodes were counted using ImageJ software. The above experiments clarified the effect of MgSrCeAl-LDH nanosheets on the tubule formation ability of endothelial cells after OGD / R.
[0090] The results are as follows Figure 8 As shown, Figure 8Mg2Sr obtained in Example 3 0.2 Ce 0.7 Al 0.1 -Figure of in vitro effectiveness study of LDH nanosheets. Figure 8 A is a graph of ROS levels at the cell level detected by DCFH-DA reagent. The results show that after H9C2 and MCMECs cells were stimulated by OGD / R, the endogenous ROS levels increased. However, Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH nanosheet pretreatment significantly inhibited the level of endogenous ROS (corresponding to OGD / R+LDH in A); Figure 8 B is a diagram of the formation of MCMEC endothelial cells using matrix gel. The results show that after OGD / R stimulation, the tubule formation ability of MCMECs cells is reduced. However, Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH nanosheet pretreatment significantly improved the angiogenic ability (corresponding to OGD / R+LDH in B); Figure 8 Figure C is a scratch test to detect the migration ability of endothelial cells. The results show that after OGD / R stimulation, the migration ability of MCMECs cells decreased. However, Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH nanosheet pretreatment significantly improved the migration ability of MCMECs cells (corresponding to OGD / R+LDH in C); Figure 8 D and E are statistical graphs of the intensity of the fluorescence image in Figure A using Imag J software. Figure 8 F and G are the statistical diagrams of the number of tubule branches and the total length of tubules in Figure B using Imag J software. Figure 8 H is a statistical diagram of the quantitative analysis of the scratch healing area in Figure C using Imag J software. Figure 8 It can be seen that Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH not only has good ROS scavenging ability in vitro, but also promotes endothelial cell migration and promotes tubule formation.
[0091] Test Example 3 In vivo effectiveness study
[0092] Study on the effect of improving heart function
[0093] (1) Establishment of MIRI animal model: 8-week-old SD male rats were used as model animals. After being fed with a normal diet for one week, they were anesthetized by inhalation of 2% isoflurane and fixed on the animal experimental table in the supine position. The skin above the xiphoid process was prepared and disinfected with iodine. The fourth intercostal space was opened on the left side of the sternum, and positive pressure artificial respiration was performed with a DW-3000B rat ventilator to maintain respiratory continuity. The great cardiac vein between the left atrial appendage and the conus arteriosus was used as a landmark. The needle was inserted 2 to 3 mm below the lower edge of the left atrial appendage and removed from the conus arteriosus. The left anterior descending coronary artery (LAD) was ligated with 6-0 non-absorbable sutures. After ligation, local myocardial changes were observed. The successful occlusion of the LAD was confirmed by ST segment elevation and the change of ventricular color from bright red to dark red on the electrocardiogram. It was then removed 30 minutes later to allow reperfusion. At the same time, the control group (Sham group) underwent the same surgical procedure, but without ligation of the left anterior descending coronary artery (LAD).
[0094] (2) Group intervention: The model mice were randomly divided into MIRI, MIRI+PBS, and MIRI+LDH groups. The MIRI group received no intervention after reperfusion. The MIRI+PBS group received 30 μL PBS injected into two sites in the ischemic myocardial border zone (15 μL at each site) immediately after reperfusion. The MIRI+LDH group received 30 μL Mg2Sr injected into the ischemic myocardium immediately after reperfusion. 0.2 Ce 0.7 Al 0.1 -LDH colloidal solution was injected into two sites of the ischemic myocardial border zone (15 μL at each site). Finally, the chest was closed routinely and squeezed during closing to avoid pneumothorax. The incisions in the surgical area were sutured layer by layer, and an appropriate amount of penicillin dry powder was sprayed on the sutured incisions. After suturing, iodine was disinfected. After the heartbeat returned to normal, the endotracheal tube was removed, and the rat MIRI model was established and the nanosheet in situ drug administration experiment was completed. All rats were kept for 2 weeks.
[0095] (3) Cardiac ultrasound examination: At 1 day, 7 days, and 14 days after the intervention, technicians who were unaware of the subject content used Vevo 2100 ultra-high resolution small animal ultrasound to perform cardiac ultrasound examination. Rats were anesthetized by 2% isoflurane inhalation, and ultrasound examination was performed after hair removal on the left chest. Parameters such as stroke volume (SV), left ventricular ejection fraction (LVEF), left ventricular fractional shortening (LVFS), left ventricular end-systolic diameter (LVIDs), and left ventricular end-systolic volume (LVESV) were recorded.
[0096] The results are as follows Fig. 9 As shown, Fig. 9 Mg2Sr obtained in Example 3 0.2 Ce 0.7 Al 0.1 -Figure of in vivo effectiveness study of LDH nanosheets. Fig. 9A is Mg2Sr 0.2 Ce 0.7 Al 0.1 -Echocardiogram of rats treated with LDH nanosheets for 1 day, 7 days, and 14 days, Fig. 9 The BF was sequentially quantitatively analyzed based on the echocardiographic results for left ventricular ejection fraction (LVEF), left ventricular fractional shortening (LVFS), left ventricular stroke volume (LVSV), left ventricular end-systolic diameter (LVIDs), and left ventricular end-systolic volume (LVESV). The results showed that at 1 day, compared with the Sham group, the LVIDs and LVESV of the MIRI, MIRI+PBS, and MIRI+LDH groups were upregulated, and significantly decreased LVEF, LVFS, and LVSV appeared, indicating that the MIRI model was successfully constructed. By 7 and 14 days, all cardiac function parameters of each group began to gradually improve, among which the MIRI+LDH group showed the most significant recovery on the 14th day. From Fig. 9 It can be seen that Mg2Sr 0.2 Ce 0.7 Al 0.1 -LDH nanosheets can significantly alleviate ischemia-reperfusion injury and enhance cardiac function.
[0097] The present invention discloses a dual-functional nanosheet and its preparation method and application. By utilizing the adjustable properties of the metal elements of the LDHs layer, the functional active component Ce is introduced into the main layer through a simple double drop method. 3+ and Sr 2+ , construct MgSrCeAl-LDH nanosheets. 3+ and Ce 4+ The redox conversion between ions enables it to have superoxide dismutase activity, which can effectively remove ROS and regulate the hypoxic microenvironment; Sr 2+ It has an activating effect on cardiovascular cells, can promote the proliferation and migration of endothelial cells and smooth muscle cells, and secrete angiogenesis-related factors to promote angiogenesis, protect the heart from coronary artery disease / reperfusion injury, and the acidic microenvironment of ischemia-reperfusion can achieve the controlled release of bioactive ions. By regulating the composition and proportion of various metal elements in the LDH layer, its anti-oxidative stress and pro-angiogenesis properties are optimized, promoting the development and application of LDHs-based nanosheets in the field of ischemia-reperfusion injury.
[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a bifunctional nanosheet, characterized in that: The following steps are involved: Mixing a soluble magnesium salt, a soluble strontium salt, a soluble cerium salt, a soluble aluminum salt and water to obtain a metal salt solution; The metal salt solution and the inorganic alkali solution are simultaneously added dropwise to the sodium nitrate solution to carry out a coprecipitation reaction, thereby obtaining the bifunctional nanosheet.
2. The preparation method according to claim 1, characterized in that: The soluble magnesium salt includes magnesium nitrate, the soluble strontium salt includes strontium nitrate, the soluble cerium salt includes cerium nitrate, and the soluble aluminum salt includes aluminum nitrate.
3. The preparation method according to claim 1 or 2, characterized in that: In the metal salt solution, the molar ratio of the soluble magnesium salt, the soluble strontium salt, the soluble cerium salt and the soluble aluminum salt is 2:0.2:0.1-0.75:0.05-0.
7.
4. The preparation method according to claim 3, characterized in that: In the metal salt solution, the total concentration of soluble magnesium salt, soluble strontium salt, soluble cerium salt and soluble aluminum salt is 0.1-0.3 mol / L.
5. The preparation method according to claim 1, characterized in that: The concentration of the inorganic alkali solution is 0.1-0.4 mol / L; the inorganic alkali in the inorganic alkali solution includes sodium hydroxide.
6. The preparation method according to claim 1, characterized in that: The concentration of the sodium nitrate solution is 0.1-0.3 mol / L.
7. The preparation method according to claim 1, 2, 4, 5 or 6, characterized in that: The volume ratio of the metal salt solution, the inorganic alkali solution and the sodium nitrate solution is 1:1:
1.
8. The preparation method according to claim 1, characterized in that: The coprecipitation reaction is carried out at room temperature and lasts for 20 to 30 minutes.
9. The bifunctional nanosheet prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The bifunctional nanosheet has a sheet-like morphology, a particle size of 100 nm, and a thickness of 3 nm.
10. Use of the dual-functional nanosheet according to claim 9 in preparing a preparation for treating myocardial ischemia-reperfusion injury.
Citation Information
Cited By
Targeted nano-enzyme with catalytic antioxidant activity as well as preparation method and application of targeted nano-enzyme
CN122297711A
